A COMPARATIVE STUDY OF OUTCOME OF IMMEDIATE CHOLECYSTECTOMY VS INTERVAL CHOLECYSTECTOMY IN ACUTE CALCULUS CHOLECYSTITIS (The Research of Medical Science Review, 2025)
Objective: To compare the outcomes of immediate cholecystectomy vs interval cholecystectomy in acute calculus cholecystitis Study design: A Prospective Cohort Study Settings: Department of General Surgery CMH, Lahore. Materials & Methods: Total sample size of 70 patients (35 in each group) was included in our study. Patients of both genders are of age 18 years and above suffering from acute calculus cholecystitis, confirmed by clinical, laboratory, and radiological criteria, were included. Patients in the immediate cholecystectomy group underwent surgical removal of the gallbladder within 24 to 72 hours of diagnosis, while those in the interval cholecystectomy division received conservative management initially, which is followed by elective cholecystectomy with the resolution of acute symptoms, typically within 4 to 6 weeks. The primary result measures include duration of hospital stay and postoperative complications. Analysis was performed with IBM SPSS, version 27.0. A p-value < 0.05 was considered to be significant. Results: The mean age of patients undergoing early cholecystectomy was 41 ± 10 years, while in the late cholecystectomy group, it was 43 ± 11 years. The commonest age of presentation is 31 to 50 years which is 70% of patients in our study group with 70% female patients and 30% male patients. Predominantly, laparoscopic cholecystectomy was performed in both early (94.3%) and late (82.9%) cholecystectomy groups. The Conversion of laparoscopic to open cholecystectomy rate was 5.7% in early cholecystectomy group as compared to 17.1% in late cholecystectomy group in our investigation. Conclusion: In conclusion, early cholecystectomy for acute cholecystitis with cholelithiasis is secure and easy, with the extra benefit of shorter duration of hospital. Although it should be offered to the patients with acute cholecystitis, such that the surgery is performed within 72 hours of acute symptoms by a qualified surgeon.